Existence of Solutions for a Fractional Boundary Value Problem at Resonance - S. Silva, Anabela (Armenian Journal of Mathematics, 2022)
In this paper, we focus on the existence of solutions to a fractional boundary value problem at resonance. By constructing suitable operators, we establish an existence theorem upon the coincidence degree theory of Mawhin.